Redistributing income under fiscal vertical imbalance - Laurent Bouton; Marjorie Gassner; Vincenzo Verardi (Luxembourg Income Study (LIS), 2007)
From the literature on decentralization, it appears that the fiscal vertical imbalance is somehow inherent to multi-level governments. Using a stylized model we show that this leads to a reduction in the extent of redistributive fiscal policies if the maximal tolerable size of government has been reached. To test for this empirically we use some high quality data, from the LIS dataset, on individual incomes. The results are highly significant and point in the direction of our theoretical predictions.
Keywords: H11; H77; I38; 330; Vertical Fiscal Imbalance; Income Inequality; Fiscal Federalism